Windows Vista ultimate bible - Durham, Joel (Wiley Pub., Inc, 2007)
The ultimate book on the ultimate Vista for gamers and digital media buffs. If you're the ultimate gamer and multimedia fan, Windows Vista Ultimate and this information-packed book are for you.